PROPERTIES OF THE COMPLEX BETWEEN ou-MACROGLOBULIN AND THE PROTEINASE BRINASE FROM ASPERGILLUS ORYZAE - Larsson, L J; Frisch, E P; Bjoörk, I (Thrombosis and Haemostasis, 1987)
Brinase, a proteinase from Aspergillus oryzae, has previously been shown to have a significant thrombolytic effect in patients suffering from peripheral arterial disease. Brinase is rapidly bound to α1-proteinase inhibitor and α2-macroglobulin (α2M) in plasma. Since binding of a proteinase to α2 M only results in ste-rical blockingof the active siteand not complete inactivation of the enzyme, it has been suggested that brinase in complex with α2M may retain ability to digest fibrin.To test this hypothesis, we have characterized the binding of brinase to α2M and the properties of the complex formed. Analyses by several techniques showed that one molecule of α2M can maximally bind twomolecules of brinase. The bait region and the thioester bonds of α2M were cleaved in this reaction in a similar manner as in the reactionwith trypsin. Moreover, a conformational change highly similar to that-caused by trypsin was induced in oα2M by brinase, as shown by changes of fluorescence emission, far-u.v. circular dichroism and u.v. absorption difference spectra. Thus, brinase appears to bind to α2M in the same manner as other proteinases. The activities of free brinase and two forms of brinase-α2M complex, produced by reaction of thetwo components in an equimolar ratio or by saturation of inhibitor with enzyme, were compared by two different assays with high-molecular-weight substrates, i.e. hide powder azure or fibrin. The complex formed with equimolar amounts of brinase and α2M showed ∼15% of the activity of free brinase in both assays, whereas the complex formed at saturation of inhibitor with enzyme showed ∼35% of the free brinase activity. Although the brinase-α2M complex, like other α2M proteinase complexes, is eliminated rapidly from plasma, the anility of the complex to cleave high-molecular-weight substrates may be an explanation of the thrombolytic effect of brinase seen in patients.